Probiotic assessment of Enterococcus durans 6HL and Lactococcus lactis 2HL isolated from vaginal microflora - Nami, Yousef; Abdullah, Norhafizah; Haghshenas, Babak; Awang Biak, Dayang Radiah; Rosli, Rozita; Khosroushahi, Ahmad Yari (Society for General Microbiology, 2014)
Forty-five lactic acid bacteria (LAB) were isolated from the vaginal specimens of healthy fertile women, and the identities of the bacteria were confirmed by sequencing of their 16S rDNA genes. Among these bacteria, only four isolates were able to resist and survive in low pH, bile salts and simulated in vitro digestion conditions. Lactococcus lactis 2HL, Enterococcus durans 6HL, Lactobacillus acidophilus 36YL and Lactobacillus plantarum 5BL showed the best resistance to these conditions. These strains were evaluated further to assess their ability to adhere to human intestinal Caco-2 cells. Lactococcus lactis 2HL and E. durans 6HL were the most adherent strains. In vitro tests under neutralized pH proved the antimicrobial activity of both strains. Results revealed that the growth of Escherichia coli O26, Staphylococcus aureus and Shigella flexneri was suppressed by both LAB strains. The antibiotic susceptibility tests showed that these strains were sensitive to all nine antibiotics: vancomycin, tetracycline, ampicillin, penicillin, gentamicin, erythromycin, clindamycin, sulfamethoxazole and chloramphenicol. These data suggest that E. durans 6HL and Lactococcus lactis 2HL could be examined further for their useful properties and could be developed as new probiotics.